1994
DOI: 10.1111/j.1349-7006.1994.tb02895.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Incidence of Loss of Heterozygosity on Chromosome 16q between Intraductal Papilloma and Intracystic Papillary Carcinoma of the Breast

Abstract: Loss of heterozygosity (LOH) on chromosome 16q was examined in DNA isolated from 11 intraductal papillomas and 12 intracystic papillary adenocarcinomas of the breast. Such LOH was detected in 8 (67%) out of 12 intracystic papillary adenocarcinomas, and in 7 (64%) of 11 of these adenocarcinomas of low grade atypia (Grade 1), whereas it was not detected in 11 intraductal papillomas. Therefore, inactivation of tumor‐suppressor genes on chromosome 16q was suggested to be involved in acquisition of malignant phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…In our previous studies, we examined LOH on 16q in intracystic papillary tumors by Southern blot analysis using frozen tissue samples [3,5] and determined that the incidence of LOH on 16q is strikingly different between cases of DCIS and papilloma [1,7]. In the present study, we performed PCR-based LOH analysis using DNA isolated from formalin-fixed, paraffin-embedded samples from CNB specimens of intraductal papillary tumors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our previous studies, we examined LOH on 16q in intracystic papillary tumors by Southern blot analysis using frozen tissue samples [3,5] and determined that the incidence of LOH on 16q is strikingly different between cases of DCIS and papilloma [1,7]. In the present study, we performed PCR-based LOH analysis using DNA isolated from formalin-fixed, paraffin-embedded samples from CNB specimens of intraductal papillary tumors.…”
Section: Discussionmentioning
confidence: 97%
“…Loss of heterozygosity (LOH) on chromosomes 16q and 17p are frequent in both invasive carcinoma and ductal carcinoma in situ (DCIS), irrespective of differences in the histological types and grades [1][2][3][4][5][6][7][8]. Several studies have reported a striking difference in the incidence of LOH on 16q between DCIS and intraductal papilloma [1,5,7] and have suggested that analysis of LOH on chromosome 16q could be helpful in the differential diagnosis of intraductal papillary tumors. In a previous study, we used Southern blot analysis to examine LOH on 16q in intracystic papillary tumors using DNA isolated from frozen, paired, surgically resected samples of tumor and non-tumor tissues [7].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Especially among intracystic papillary tumors, LOH on chromosome 16q is not detected in papillomas but is detected in > 70% of cases of intracystic papillary carcinoma showing low grade atypia; they are often difficult to differentiate from papillomas. 14 Although, in the present study, those kinds of problematic cases were not included, examination of LOH on 16q in preoperative fine needle aspiration materials from intracystic papillary tumors using the present method would be helpful for judging the nature of the tumors.…”
Section: Discussionmentioning
confidence: 99%
“…6,10,[12][13][14] Such LOH can also be examined in a small amount of DNA by the polymerase chain reaction (PCR) using oligonucleotide primers that encompass (AC) n repeat sequences located in the noncoding DNA regions of chromosomes. 7,11 Because the number of repeated adenine-cytosine sequences in (AC) n regions frequently differs between individuals, these regions are very informative for detection of LOH in cancer tissue.…”
Section: Objective: To Clarify Whether Analysis Of Loss Of Heterozygomentioning
confidence: 99%
“…Data also suggests that loss of heterozygosity (LOH) on chromosome 16q is a useful marker for IPC, unlike intraductal papilloma which does not exhibit such characteristics. The use of polymerase chain reaction indicates in a more definite way the potential of malignancy in intracystic papillary lesions, as 16q LOH depicts malignancy [20]. [39].…”
Section: Mammographymentioning
confidence: 99%